Pengaruh Orientasi Kewirausahaan, Media Sosial Dan Lingkungan Keluarga Terhadap Intensi Berwirausaha (Studi Kasus Mahasiswa STMB Multi Smart) - Halawa, Niati; Fitra Uli Tamba, Iventura; Hidayat, Ferry (VALUE, 2025)
Thisistudy aims to determine the effect of entrepreneurial orientation, social media, and family environment on entrepreneurial intentions in STMB MULTI SMART students. Specifically, this study examines ithe iinfluence iof eachi variablei partially ior simultaneously ion ithe formation of entrepreneurial intentions. The approach used iis quantitative descriptive with correlational research methods. The population in this study were all STMB MULTI SMART students totaling 316 people. The sample determination was carried out using random sampling techniques using the Slovin formula, so that a sample of 76 students was obtained. Datai analysis techniques used include validity tests, reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity, and linearity), and multiple linear regression analysis. The results of the study indicate that partially, entrepreneurial orientation, social media, and family environment have a positive and significant effect on entrepreneurial intentions. Simultaneously, the three variables also have a significant effect on students' entrepreneurial intentions. These findings indicate that internaliand external factors have an important role in encouraging students' intentions to become entrepreneurs